Investigation of the Impact of Selected Monetary Variables on Capital Market Performance - Mansouri Bidkani, Mahdi; Barahooeijahanshahi , Ali; Faraji, Amirhossein; Bahrami , Mohammad Kaveh; Khosravi, Saeid (Management Strategies and Engineering Sciences, 2025)
This research aims to investigate the impact of monetary variables on stock market performance. Monetary variables can directly or indirectly affect stock market performance. This study focuses on the impact of interest rates, exchange rates, inflation rates, liquidity, and the legal reserve ratio on the stock price index. Another objective of this research is to examine the impact of economic policy uncertainty on the relationship between monetary variables and the overall stock price index, as well as to analyze how monetary variables are managed and their influence on the stock market. The research period spans ten years, from 2013 to 2022. The hypothesis testing results, using seasonal time series data and the Autoregressive Distributed Lag (ARDL) model, showed that the impact of money supply and exchange rates on the overall stock price index is positive and significant, while the effects of the interest rate index and the legal reserve ratio are not significant. Furthermore, this research, based on an index for economic policy certainty, indicates that the relationship between interbank interest rates, money supply, legal reserve ratio, and exchange rates with the overall stock price index is influenced by economic policy uncertainty.